Electrical Activities and Pressure Pain Threshold in Oral Contraceptives Users and Nonusers - Turcio, Karina Helga Leal; Garcia, Alício Rosalino; Zuim, Paulo Renato Junqueira; Sundefeld, Maria Lucia Marçal Mazza; Goiato, Marcelo Coelho; dos Santos, Daniela Micheline (Scientific Research, 2014)
The aim is to evaluate the influence of oral contraceptive intake and menstrual cycle on the electrical activity and pressure pain threshold from anterior temporal and masseter muscles. Twenty-eight women on reproductive age were selected, 13 OC users and 15 nonusers. They were weekly submitted to electromyography and algometry of the anterior temporal and masseter muscles during three consecutive menstrual cycles. Electrical activities at rest position and PPTs of temporal and masseter muscles were not affected by menstrual cycle or by OCs uses. Comparison between groups demonstrated that working side electrical activity was increased in OC users in both muscles, except during lutheal phase for the anterior temporal. However, comparison within weeks did not demonstrate statistical difference. It was suggested that, in healthy women, oral contraceptive use may influence electrical activity, but different phases of the cycle may not.
Keywords: Menstrual Cycle; Pressure Pain Threshold; Electromiography; Oral Contraceptives; Sexual Hormones